What Is Recent in Pancreatic Cancer Immunotherapy?. (26th December 2012) - Niccolai, Elena; Prisco, Domenico; D'Elios, Mario Milco; Amedei, Amedeo
Abstract : Pancreatic cancer (PC) represents an unresolved therapeutic challenge, due to the poor prognosis and the reduced response to currently available treatments. Pancreatic cancer is the most lethal type of digestive cancers, with a median survival of 4–6 months. Only a small proportion of PC patients is curative by surgical resection, whilst standard chemotherapy for patients in advanced disease generates only modest effects with considerable toxic damages. Thus, new therapeutic approaches, specially specific treatments such as immunotherapy, are needed. In this paper we analyze recent preclinical and clinical efforts towards immunotherapy of pancreatic cancer, including passive and active immunotherapy approaches, designed to target pancreatic-cancer-associated antigens and to elicit an antitumor response in vivo .